2008
DOI: 10.1111/j.1745-7270.2008.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression profiling of human epidermal growth factor receptor 2-overexpressing mammary tumor

Abstract: Human epidermal growth factor receptor 2 (HER2) is highly expressed in approximately 30% of breast cancer patients, and substantial evidence supports the relationship between HER2 overexpression and poor overall survival. However, the biological function of HER2 signal transduction pathways is not entirely clear. To investigate gene activation within the pathways, we screened differentially expressed genes in HER2-positive mouse mammary tumor using two-directional suppression subtractive hybridization combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…During our premier study, an important RNA gene named Z38 was isolated from breast cancer by combining SSH and reverse dot-blotting 35 , and it was one of the identified genes, of which differentially expressed in mammary tumor. However, the discovery of Z38 was not published all the time in consideration of our current research work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During our premier study, an important RNA gene named Z38 was isolated from breast cancer by combining SSH and reverse dot-blotting 35 , and it was one of the identified genes, of which differentially expressed in mammary tumor. However, the discovery of Z38 was not published all the time in consideration of our current research work.…”
Section: Resultsmentioning
confidence: 99%
“…The detailed methods of SSH and reverse dot-blotting were described in one of our published articles 35 . In brief, total RNA and poly (A) tract mRNA was isolated from mammary tumor specimens of MMTV-neu mice and normal mammary tissues of FVB mice.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, they may act as tumor markers (10,11). Indeed, in a previous study, Wang et al (12) identified that the expression of IFITM2 protein was significantly increased in HER2-overexpressing mouse mammary tumors, while other investigators proposed that IFITM3 protein may be involved in diverse cellular processes (7,13,14), including immune-cell regulation, somitogenesis, germ cell homing and maturation, cell proliferation (15) and heart development (16). Previous studies demonstrated that IFITM3 expression was significantly upregulated in colorectal cancer (10) and played a critical role in regulating tumor cell migration and invasion, which contribute to the progression of gastric and head and neck cancers (17,18).…”
Section: Introductionmentioning
confidence: 96%
“…HER2 lacks the ability to interact with ligand, and is often activated via dimerization with other ErbB receptors, such as epidermal growth factor receptor (EGFR) or HER3 [2]. HER2 oncoprotein overexpression is often correlated with the growth, metastasis, and therapeutic resistance [3,4]. Accumulated clinical and laboratory evidences have indicated that overexpression of HER2/neu may render tumor cells resistant to several anticancer drugs such as paclitaxel (Taxol), cyclophosphamide (CTX), methotrexate (MTX), 5-fluorouracil (5-FU), epirubicin, and so on [5][6][7].…”
Section: Introductionmentioning
confidence: 99%